Children’s Preparedness through Disaster Response Training in Sentra of Drama TKIT Baitussalam 2 Cangkringan Sleman - Cahyani, Widia Arinta; Windiarti, Rina (Jurusan PGPAUD FIP UNNES, 2017)
A disaster is an event that can happen anywhere, anytime and overwrite anyone. For it is necessary preparation for the community in the area of disaster-prone to know what things to do in facing disaster. This study aims to measure the level of disaster preparedness in children through disaster response training in drama centers TKIT Baitussalam 2 Cangkringan Sleman. Through disaster response training, it can be known whether or not there is a difference in the level of preparedness of children.The method used in this study is experimental. Research using one group pretest posstest design that experiments conducted in a single group without a comparison group. The research instrument with preparedness parameter is using Guttman scale with a straight answer